Founders and organizational development : the etiology and theory of founder's syndrome - Block, Stephen R.; Miller-Stevens, Katrina (New York, NY : Routledge, 2021)
"Founders and Organizational Development: The Etiology and Theory of Founder's Syndrome is designed to help today's researchers, faculty, students and practitioners become familiar with the etiology and dynamics of Founder's Syndrome as an organizational condition challenging nonprofit/nongovernmental, social enterprise, and for-profit and publicly traded organizations. The book uses applied social and psychological theories and concepts to peel away the layers of an organizational enigma, revealing three causes of Founder's Syndrome and insight into the power and privileges assumed by founders who engage in undesirable and self-destructive behaviors leading to their termination; going from hero status to antihero. Researchers, instructors, students, and practitioners will find thought-provoking case studies from the real world of organization development practice. Segments from interviews during interventions reveal the type of emotional turmoil experienced in organizations where founder's syndrome is present. Insight is provided into accounts of well-known founders who were terminated or forced to resign. The unique features of this book include: integrating theory into practice, describing a new theory about the psychological reaction of founder's syndrome victims, prevention ideas when designing new organizations, strategies for intervention, using content based on research and organization development consultation experiences, and, integrating feedback from students who have launched organizations"--
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Management; New business enterprises; Entrepreneurship; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Leadership